The effect of molten salt on the mechanical properties and microstructure of CuNiSi alloys with reinforced Fe - Akkaş Mehmet (National Library of Serbia, 2024)
In this study, CuNiSi alloys were produced using powder metallurgy in molten salt (KBr). In the Cu, Ni, and Si powder mixture, Fe was added at a rate of 2.5%, 5 and 7.5% and mechanical alloying was carried out for 4 hours at 400 rpm. Prepared powder mixtures were cold pressed under 600 MPa pressure and sintered for 3 hours at 900? in an argon atmosphere. Phase formation, microstructure, microhardness, electrical conductivity, and corrosion of the produced samples were analyzed in detail. Scanning electron microscope (SEM) was used to detect the changes in the microstructure of the produced samples, and an X-ray diffractogram (XRD) was used to determine the phases formed in the internal structure of the materials. In order to determine the mechanical properties of the produced samples, hardness analyzes were made with a microhardness measuring device. The electrical conductivity properties of the produced CuNiSi and CuNiSiFe alloys were determined due to the increase in the Fe ratio. Corrosion tests of the produced samples were determined by potentiodynamic polarization curves in a 3.5% NaCl solution. Fe-reinforced CuNiSi composite materials have been successfully produced in molten salt (KBr). CuNiSi alloy, the microstructure is dominated by the typical large and small particles. Fe element is homogeneously dispersed in the CuNiSi alloy instead of being separated using the Ni element. Fe particles have decreased the hardness of produced alloys. The electrical conductivity properties changed with increasing voltages depending on the increase of Fe supplementation, and as a result, the sample containing 7.5% Fe had the best electrical conductivity values. Results showed that by increasing the amount of Fe, the mechanical properties and corrosion resistance increased.
Keywords: powder metallurgy; cunisi alloy; corrosion; Chemical technology; TP1-1185; mechanical alloying; hardness